Super Enhancer Profiles Identify Key Cell Identity Genes During Differentiation From Embryonic Stem Cells to Trophoblast Stem Cells Super Enhencers in Trophoblast Differentiation - Jia, Rongpu; Gao, Yu; Guo, Song; Li, Si; Zhou, Liangji; Gou, Chenyu; Huang, Yijuan; Fan, Meiqiong; Chen, Yuanqiu (Frontiers in Genetics, 2021)
Trophoblast stem cells (TSCs) are derived from embryonic stem cells (ESCs) and play a significant role in fetal development, and the roles that TSCs play in the earlier status of fetal diseases need further exploration. Super enhancers (SEs) are dense clusters of stitched enhancers that control cell identity determination and disease development and may participate in TSC differentiation. We identified key cell identity genes regulated by TSC-SEs via integrated analysis of H3K27ac and H3K4me1 chromatin immunoprecipitation sequencing (ChIP-seq), RNA-sequencing (RNA-seq) and ATAC-sequencing (ATAC-seq) data. The identified key TSC identity genes regulated by SEs, such as epidermal growth factor receptor (EGFR), integrin β5 (ITGB5) and Paxillin (Pxn), were significantly upregulated during TSC differentiation, and the transcription network mediated by TSC-SEs enriched in terms like focal adhesion and actin cytoskeleton regulation related to differentiation of TSCs. Additionally, the increased chromatin accessibility of the key cell identity genes verified by ATAC-seq further demonstrated the regulatory effect of TSC-SEs on TSC lineage commitment. Our results illustrated the significant roles of the TSC-SE-regulated network in TSC differentiation, and identified key TSC identity genes EGFR, ITGB5 and Pxn, providing novel insight into TSC differentiation and lays the foundation for future studies on embryo implantation and related diseases.